faktor – faktor yang mempengaruhi dividen tunai pada perusahaan industri rokok yang terdaftar di bursa efek indonesia - Siti Nur Aini (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study was to determine the effect of variable Current Ratio, Return On Investment (ROI), Total Assets Turn Over (TATO) And Earning Per Share (EPS) jointly affect the cash dividend on the company's cigarette industry listed on the stock exchanges of Indonesia and variable as well as the dominant influence on the cash dividend. The analytical tool used in this research is multiple linear regression.Based on the results of analysis show that the results showed that the regression equation y = 2,997 X1 + 0.092 X2 + 0.023 + 0.041 + 0.040 X3 X4 means that any changes in variables have an influence on Cash dividends (Y). it is supported R2 value of 0331, or 33.10%, which means a cash dividend amounting to 33.10% influenced by these variables and the rest influenced by factors - other factors not examined in this study.The results of t-test showed four variables corrent Ratio penlitian show that the dominant influence on the company's cash dividend for the cigarette industry listed in Indonesia Stock Exchange.Keywords:     Corrent Ratio, Return On Investment (ROI), Total Assets Turn Over (TATO), And Earnings Per Share (EPS) And Dividend.